A Case Study of the Risk and Crisis Communications Used in the 2008 Salmonella Outbreak - Ashley Palmer; Erica Irlbeck; Courtney Meyers; Todd Chambers (Journal of Applied Communications, 2013)
The Salmonella outbreak of 2008 was one of the largest foodborne illness outbreaks in the last 20 years. Tomatoes were initially pinpointed as the source of the outbreak, and the tomato industry suffered losses of $100 million in 2008. Eventually the FDA was able to trace the outbreak to imported jalapeño peppers, but this discovery was too late to recover losses for the tomato industry. The purpose of this study was to examine the risk and crisis communication efforts taken by public relations practitioners in the produce industry during the 2008 Salmonella outbreak to determine which efforts were successful and which were ineffective. This qualitative case study used the interviews of nine public relations practitioners in the tomato industry to collect the information needed to fully explore the research objectives of the study. The study found that all of the public relations practitioners attempted to communicate effectively with their audiences despite the negative nature of the 2008 Salmonella crisis. Additionally, the practitioners revealed their thoughts and perceptions about the outbreak, the media, and the communications used during the outbreak, which provided valuable insight into the communication efforts of an organization during a crisis.
Keywords: risk & crisis; foodborne illness; Salmonella; Excellence theory